Transformasi Resistensi Perempuan dalam Novel Sitti Nurbaya Karya Marah Rusli ke Serial Musikal Nurbaya - Ajeng Restiyani; Suma Riella Rusdiarti (Universitas Mulawarman, 2023)
This study aims to dismantle the strengthening of patriarchal culture and its impact on women’s position in the adaptation of the Sitti Nurbaya novel by Marah Rusli to the Nurbaya musical series directed by Naya Anindita and Venytha Yoshianthini and broadcast on Indonesia Kaya Youtube channel. The research method used is analytical descriptive by applying the concept of ecranisation, a feminist approach and aspects of musicality in musical theater, in addition to digital cinematography as readings of a film theater. The results show the transformation of the main female character’s resistance to patriarchal culture in novels and musical series. In the novel, resistance is targeted at criticism of domestic practices in the household. In contrast, in musical theater the resistance is extended to contemporary issues, namely dreams of freedom and ideals. In addition, the resistance of the main female character also shows her agency, which can influence other oppressed women to fight back. However, despite the transformation of resistance, the adaptation still reflects the strengthening of patriarchal culture. In the musical series, the patriarchal culture that occurs is not only carried out by male domination but by the involvement of women in strengthening patriarchal domination.